Implementation of the Duties of the Satlantas Regident Unit in Identifying Motorized Vehicles and Drivers at the Buleleng Resort Police - Jody Arya Sejati, Kadek; Sihotang, Erikson; Suandika, I Nyoman (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The role of the registration and identification unit in serving documents as evidence of law enforcement at Buleleng District Police. There are still obstacles in presenting documents as evidence of law enforcement at Buleleng Police Station, namely the non-registration of motorized vehicles in the Resident Unit database, the length of time for servicing STNK/proof of ownership of motorized vehicles, lack of public awareness about changing the name of motorized vehicles, and there is a culture of people using brokers in the process of processing motor vehicle documents. The purpose of this study was to determine and analyze the implementation of the task of the regd satlantas unit in the identification of motorized vehicles and drivers at buleleng police station. The method in this research uses normative juridical supported by empirical research. The results showed that the role of the registration and identification unit in serving documents as evidence of law enforcement at Buleleng Police Station was in the form of a. Preventive: providing motor vehicle documents in the form of STNK and BPKB services requested by the public. B. Repressive: issuing information letters requested by Bareskrim regarding criminal acts related to motorized vehicles (as evidence). This research has implications for increasing the effectiveness and efficiency of the registration and identification unit at Buleleng Police Station in serving documents as evidence for law enforcement.